Detection of viral infectious agents causing calf diarrhea on dairy farms in Serbia - Milicevic, V; Kureljušić, B; Glišić, D; Veljović, L; Maletić, J; Jezdimirović, N; Maletić, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Neonatal calf diarrhea (NCD) is a multifactorial disease commonly occurring in unweaned calves, and one of the major causes of calflosses worldwide. In this study, we investigated the role of viral agents in neonatal calf diarrhoea from dairy farms with reported outbreaks in the winter of 2021-2022.For this study, we tested rectal swab samples from 20 commercial dairy farms with 100-1000 cows with reported acute diarrhoea in neonatal calves.From each farm, five to ten calves, up to 2 months of age, in total 154, with acute diarrhea were sampled by rectal swabbing. Out of 20 tested dairy farms, at 4 farms none of the testedviruses was detected whereas at least one of the tested viruses was detected at 16 farms (80%). As the most prevalent, mono BRV infection was detected at 10 farms (62.5%), followed by a single BCoV infection at 3 farms (18.75%). Coinfection of BVDV and BRV was demonstrated at 2 farms (12.5%), and simultaneous infection with BVDV, BRV and BCoV at one farm (6.25%). G typing of BRV revealed that 60% of the BRVs were G10, 33.3% were G6, and 16.7% were G8. P typing indicated that 66.7% of the BRVs were P[11] and that 33.3% were P[5]. This study revealed viral causative agents being the most often found in diarrheic neonatal calves in Serbia, thuscontributing to the development of more effective strategies for disease prevention and control.